Pengelolaan keuangan desa berdasarkan asas transparansi, akuntabel, partisipatif, tertib dan disiplin anggaran - Yulia Riska Manik; Arthur Simanjuntak; Duma Megaria Elisabeth (Jurnal Ilmiah Bisnis dan Perpajakan (Bijak), 2026)
This study aims to determine the effect of Transparency, Accountability, Participation, Orderliness, and Budget Discipline on Village Financial Management in Hudopa Nauli Village, District, Central Tapanuli Regency. This research is quantitative in nature and uses primary data. The population in this study consists of all village officials in Hudopa and the community, with a sample of 37 respondents selected using purposive sampling. Data collection was conducted by distributing questionnaires to village officials and community members directly involved in village financial management. The data analysis technique used in this study is descriptive statistics. The quality of primary data was tested by the researcher using validity and reliability tests, classical assumption tests, multiple linear regression tests, and hypothesis testing using the SPSS 25 application. The results of this study individually show that Transparency and Participation have a positive and significant effect on Village Financial Management. Meanwhile, Accountability and Budget Order and Discipline do not have a significant effecton Village Financial Management.